Differences in Sesbania sesban accessions in relation to their phenolic concentration and HPLC fingerprints - Heering, H.; Reed, J.D.; Hanson, Jean (Wiley, 1996)
Phenolic concentration in the leaves from 103 different accessions of Sesbania sesban (L) Merr was determined and HPLC was used to analyse the extractable phenolics. The chromatograms were subjected to cluster analysis. large variation was observed between accessions in the soluble phenolic and insoluble proanthocyanidin concentrations. The study further showed that the accessions could be grouped on the basis of their HPLC fingerprints. The results suggest that quantitative and qualitative selection for polyphenolics is possible. This type of information is relevant to future programs aimed at the improvement of the nutritive value in Sesbania sesban.